Cellular interactions in antibody production - Howie, S; Feldmann, M (1978)
The article is a survey of the cellular interactions in the humoral response to antigen, the role of the major histocompatibility complex in the response, and the antibody response to antigens under the control of histocompatibility-linked immune response (Ir) genes. The article includes chapters on hapten-carrier effects and on the role of the major histocompatibility complex in T- and B-cell co-operation. Furthermore, macrophage-T-cell interactions, T-T cell interactions, and T-cell-macrophage-B-Cell interactions are discussed. There are 84 references.